SISTEM INFORMASI PENDAFTARAN SISWA BARU BERBASIS ONLINE - Sunardi, Sunardi; Rusdan, Rusdan; MZ, Dedy Sofian; Indrayatni, Baiq Intan (JUTECH : Journal Education and Technology, 2024)
Vocational schools are high schools based on hard skills, including SMK NW Korleko. As the number of students increases, it becomes difficult for schools to manage data on students who register, and making reports takes a long time. When accepting new students, the school still uses a manual system: prospective students fill out a paper form. Based on the problems faced, this research aims to help schools manage student data while admitting new students using the website. The method used in this research is the waterfall method, which has sequential stages, namely needs analysis, design, coding, testing, and maintenance. Meanwhile, the programming language for building the system uses PHP, and the DBMS uses MySQL, which is compatible with developing website-based applications. The results of this research are in the form of a web-based information system for new student admissions, which can help make it easier for students to register and for schools to carry out new student admission activities online.